STUDY ON DIRECTOR'S POLICY ON DISCHARGE WAITING TIME OF INPATIENTS IN UNIVERSITY OF MUHAMMADIYAH MALANG HOSPITAL - Anwar, Jamilatus Syamsiah; Mansur, Muhammad; Djamhuri, Ali (Jurnal Aplikasi Manajemen, 2017)
Completion inpatient discharge administration is a combination of some unit performance in services of a particular patient in a hospital. Delay in inpatient discharge due to delays in the completion process of administration have an impact such as prolong the waiting time of inpatient discharge. Waiting time can change patient's perception of the service quality of RS UMM. This study aims to determine the difference between waiting time of inpatient discharge service before and after enactment of director policy administration. This study is descriptive research with the research design use pre and post intervention. Development of data use observation in three (3) point of research, that is the ward, pharmacy, and cashier. The relationship between the director policy with inpatient discharge waiting time in RS UMM tested by using independent T-test in statistical software SPSS 20.0.The result showed no difference between waiting time of inpatient discharge services before and after implementation of director policy administration, although the data obtained that the waiting time before greater than waiting time after enactment of director policy administration (3,222 hours > 2,802 hours). The process of observation found another factor that suspected to affect the administrative process, they are the time of visiting from specialist over at 20.00 and under 07.00, the giving information of discharge patient not by the doctor in charge, a weak system of evaluation program by the managerial, and manufacture of prescription drugs that are not according with hospital formulary.